THE ASSOCIATION OF SERUM URIC ACID WITH NON-ALCOHOLIC FATTY LIVER DISEASE – A CASE CONTROL STUDY IN A TERTIARY HOSPITAL IN NORTH KARNATAKA - Dr. Pramila Devi R.; Dr. Sohan Channeshappa Kotigera (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND AND OBJECTIVES:Need for the study:Non alcoholic fatty liver disease is one of the most prevalent causes of liver cirrhosis in the world. [1]Cell line studies show - Higher uric acid induces hepatocyte fat accumulation. [2]Uric acid induces hepatic steatosis by generation of mitochondrial oxidative stress. [3]. This prompts the need for further research. METHODS:Source of data: The data is sourced from the patients visiting the department of General medicine in HSK Hospital, SNMC, Bagalkot.Inclusion criteria:Adults - aged more than 18 and less than 60 years.Cases – ultrasonological features of fatty liver.Controls – Age and gender matched individuals with no ultrasonological liver abnormality.Exclusion criteria:• History of alcohol consumption.• Hepatitis B or Hepatitis C reactive patients.• Those suffering from viral hepatitis.• History of cancer.• Those on medications that lead to hyperuricemia. RESULTS: 1. The mean uric acid levels were 6.4 ± 2.3 in cases compared to 3.9 ± 1.6 in the controls. The difference in between these levels (overall) is statistically significant with a p values of